S20 Inhaled aztreonam lysine recovers lung function and improves quality of life in acute pulmonary exacerbations of cystic fibrosis. (12th November 2019) - Frost, F; Fothergill, J; Winstanley, C; Nazareth, D; Walshaw, MJ
Abstract : Background: Pulmonary exacerbations cause significant morbidity in people with cystic fibrosis, but treatment with extended courses of intravenous antibiotics may also result in systemic side-effects, adverse reactions and co-morbid complications. Treatment through the inhaled route, where the lungs are targeted directly with less systemic exposure may be more appropriate. The AZTEC-CF study investigated the efficacy of inhaled aztreonam lysine (AZLI) in the treatment of acute pulmonary exacerbations. Methods: AZTEC-CF was an open-label randomised crossover study designed and conducted at a regional adult cystic fibrosis centre in the UK ( ClinicalTrials.gov: NCT02894684 ). Inclusion criteria included age > 16 years, P. aeruginosa infection and no prior use of AZLI. Exclusion criteria included Burkholderia cepacia complex infection and solid-organ transplant. During two consecutive exacerbations requiring hospitalisation for intravenous antibiotics, subjects received 14 days AZLI plus intravenous colistimethate (AZLI+IV) or standard dual intravenous antibiotics (IV+IV). Primary outcome was recovery of% predicted FEV1 (ppFEV1) at 14 days. Key secondary outcomes included health-related quality of life outcomes, sputum bacterial load, systemic inflammatory markers, aztreonam resistance and safety outcomes. Results: Sixteen adults with CF were consented and randomised, and by March 2019 (censorship date) 28/32 (87.5%) exacerbations were completed. At 14 days, improvement in ppFEV1 was greater for AZLI +IV compared to IV+IV (mean +13.5% versus +8.3%; paired differences [95% CI] +4.6% [2.1 to 7.2], p=0.002). The minimum clinically important difference in CFQ-R Respiratory Domain was achieved more frequently in exacerbations treated with AZLI+IV (83.3% vs. 43.8%, p=0.03). No significant differences were found between treatments for changes in sputum bacterial load, systemic inflammation or adverse events. Aztreonam-resistant P. aeruginosa load was significantly increased (+0.9 Log10 CFU/ml, p=0.01) after the IV+IV treatment but not AZLI+IV (-0.15 Log10 CFU/ml, p=0.65) despite no use of aztreonam in the IV+IV treatment. Conclusion: AZLI is effective, safe and well tolerated in the treatment of acute pulmonary exacerbations of CF. Superior improvements in lung function and quality of life suggest AZLI may represent a new treatment approach for acute pulmonary exacerbations and further work is required to understand how its use in the acute setting can be optimised.